Histopathological insights into cherubism: a case presentation - Kashyap, Nikita; S., Aravindan; Rakshit, Sudipta (International Journal of Research in Medical Sciences, 2025)
Cherubism is a rare hereditary fibro-osseous disorder of the jaws, typically presents as progressive, painless, bilateral jaw swelling in children between 2 to 5 years of age, with lesions showing maximum growth until puberty before regressing spontaneously. Radiographically, it is characterized by bilateral, multilocular radiolucencies in the posterior mandible and maxilla. Histopathologically, cherubism is marked by fibrotic stromal proliferation with multinucleated osteoclast-like giant cells. The presence of vascular channels and eosinophilic deposits further accentuates the unique histologic landscape of this condition. By documenting this histopathological perspective, we aim to reinforce its diagnostic significance and contribute to the growing repository of cherubism-related literature.